'Fun, Games and Gains' in Bangkok Unlicensed Guide: Thai (Male)–Farang (Female) Sexual Encounters in 1970s Semi-Fiction. (December 2015) - Feangfu, Janit
This article investigates cross-cultural encounters from the point of view of a local man who tries to gain the upper hand in power negotiations in the context of tourism. Through titillating narratives, he constructs 'white women' as 'loose', a stereotype which remains prevalent in Thai male perceptions of Western women in the twenty-first century. The article looks at selected semi-fiction from the 1972 collection Kai-phi Bangkok chut 1 ( Bangkok Unlicensed Guide Collection 1 ) by Ta Tha-it in its capacity as a representative of the 'lowbrow' genre of 'male writing for male reading'. Exploring the narratives of sexual encounters between a local tour guide and Western women, it examines the sexualization of the farang (Western) body as a strategy for 'fun, games and gains' in cross-cultural sexual encounters. In the three stories discussed, the sexualized farang bodies turn out to be homosexual, masochistic and aged respectively, while the Thai body is hetero-normative, young and virile. The entire collection from which this analysis is drawn was composed in the 1970s against the backdrop of Cold War Thailand as an emerging tourist destination for US soldiers in Indochina and of the rise of international tourism in Thailand.